Antibacterial electroconductive rGO modified cotton fabric. (6th July 2021) - Mizerska, Urszula; Fortuniak, Witold; Makowski, Tomasz; Svyntkivska, Mariia; Piorkowska, Ewa; Kowalczyk, Dorota; Brzezinski, Stefan; Kregiel, Dorota
Abstract: Cotton fabric was modified with organosilicon coating containing graphene oxide (GO), which was then thermally reduced to reduced graphene oxide. The thermal reduction imparted electrical conductivity and hydrophobicity to the fabric. In order to augment the reduction of GO in the coating, the organosilicon sol with active reducing ─SiH groups, was synthesized from alkoxysilanes. Chemical modification of the coating with tert‐ butylamine groups and N, N‐dimethyl‐N‐n‐octylammonium groups allowed to achieve antibacterial activity of the electroconductive fabric against Escherichia coli and Staphylococcus aureus . Although the modification worsened the electrical conductivity, the coated fabric, especially that modified with tert ‐ butylamine groups, remained electroconductive.